3G networks : architecture, protocols & procedures - Kasera, Sumit; Narang, Nishit (McGraw-Hill's AccessEngineering., 2004)
In India, the mobile subscriber baser is increasing at a phenomenal rate. After the successful adoption of Second Generation (2G) Technology GSM and 2.5G Technology GPRS, the industry is now rapidly moving towards Third Generation (3G) Networks. The book, written by two young engineers, touches almost every imaginable aspect of a 3G Network, spanning across topics such as: UMTS Network Architecture (including Access Network and Core Network), Protocols (including RRC, NBAP, RANAP, MM/GMM, MAP and GTP), Procedures (including UTRAN Procedures, Mobility Management, Call/Session handling and Security Management), and Services (including Supplementary Services and Value-added Services). Also the book covers topics like IP Multimedia Sub-system (IMS) and SIGTRAN. Besides these, the book includes the status of deployment of 3G UMTS Networks across the world and provides a brief introduction to 4G Networks setting the tone for future advancements. With this coverage, the book would serve the needs of telecom engineers and students.